COUNCILS FOR INTER-ETHNIC RELATIONS AS A MECHANISAM FOR BUILDING TRUST BETWEEN COMMUNITIES IN THE CONTEXT OF MULTICULTURALISM IN SERBIA - Nenadić, Danijela (Political Review, 2024)
The stablishment of good relations between the majority and ethnic minorities, in the context of multiculturalism, is a priority in multiethnic societies such as the Republic of Serbia. The effort to build a society that all citizens perceive as “their own” and achieve a high level of identification and sense of belonging with it is at the core of all democratic societies across the world. The concepts on which modern societies are based (multiculturalism, interculturalism, etc.) and the theories based on them strive to find the best answers for societies while understanding and appreciating the differences that characterize those societies. The inclusion of all citizens and groups in social, political, institutional, economic and other flows in society increases the chances for stable functioning of states and reduces the possibility of conflict base on exclusion and/or misunderstanding and insufficient communication between groups. The paper provides insights to the meaning of multiculturalism (and interculturalism), depicts the context of Serbia as a multiethnic society, gives a theoretical background for understanding complex societies, and analyzes the Councils for Inter-Ethnic Relations as one of the mechanisms of establishing multiculturalism in Serbia. The overall argument of this paper is that multiculturalism is, in principle, the determination of Serbian society. The theoretical framework for understanding the concept of multiculturalism (and interculturalism), as well as the situation in Serbia, is briefly presented. The central part of the work concentrates on the efforts to explain the functioning of Councils for Inter-Ethnic Relations, with recommendations for the improvement of their work. The Law on Local Self-Government stipulates that Councils for Inter-Ethnic Relations (the Councils) should be established in those local self-governments that meet the legal requirements, that is, in ethnically mixed municipalities and cities. Practice and international reports, as well as data from the Special Report of Ombudsman on Council for Inter-Ethnic Relations, clearly indicate necessity to further promote establishment and efficient functioning of these bodies at the local level in all municipalities and cities with ethnically mixed population. The aim of this analysis was to assess the functionality of Councils and their role in local self-governments that have legal obligation to establish this body. In previous years, the Law on Local-Self Government was amended and supplemented in those articles related to the establishment and functioning of Councils. Those changes took, to some degree, recommendations from the previously mentioned Special Report of Ombudsman published in 2017.  Councils have not yet become bodies that would fully contribute to the realization, protection and promotion of national equality and inter-ethnic dialogue at the local level. The Analysis of the Council’s work indicated that they rarely participate in proposing or giving opinions to self-governments decisions aimed at achieving national equality or enhancing integration and tolerance. Councils often remain bodies that do not fulfil their defined role in full capacity. Future legal changes should aim at a more accurate definition of the scope of the Council’s work.
Keywords: multiculturalism; interculturalism; interethnic relations councils; national equality; trust